The interrelations between mathematics and philosophy in Leibniz´s thought - Goethe, Norma (2015)
Fil: Goethe, Norma. Universidad Nacional de Córdoba. Facultad de Filosofía y Humanidades. Escuela de Filosofía; Argentina.